A New Anticancer Tannin and known Tannins from Terminalia cattapa† - Kandil, F.E.; Soliman, A.M.; Mabry, T.J.; Skodack, S.R. (Asian Journal of Chemistry, 2010)
The structures of the new tannin and the known compounds were established on the basis of 1H and NMR analysis. The new tannin was found to have high activity against Ehrlish ascita carcinoma cells.